An In-vitro evaluation of a polyherbal formulation, against SARS-Cov-2 - Divya Kanchibhotla; Saumya Subramanian; Reddy M. Ravi Kumar; K.R. Venkatesh Hari; Monika Pathania (Journal of Ayurveda and Integrative Medicine, 2022)
Background: In the last two years, COVID-19 pandemic caused by SARS-CoV-2 has created a mass destruction among humanity causing a major health crisis around the world. With the emergence of new strains of the virus, lack of targeted drugs and antimicrobial resistance, there is a dire need to discover specific antiviral with minimum side effects targeted against COVID-19. Objective: The present study evaluates the antiviral efficacy of a novel Ayurvedic polyherbal formulation, NOQ19, composed of a 13 well known herbs, in a cell-based setting. Methodology: Vero E6 (CL1008), the African green monkey kidney epithelial cell, were infected with SARS-CoV-2 virus (isolate USA–WA1/2020) in a 96 well-plate. NOQ19 test material was diluted at different concentration: 0.05 mg/ml, 0.1 mg/ml, 0.2 mg/ml, 0.3 mg/ml, 0.4 mg/ml, 0.5 mg/ml, 0.6 mg/ml, 0.7 mg/ml, 0.8 mg/ml and 0.9 mg/ml. These different concentrations of NOQ19 were added to infected cells respectively and incubated for 3 days in 5% CO2 incubator. Remdesivir was used as a positive control. The cells were finally fixed with formaldehyde, stained with crystal violet and plaques were visualized. The number of plaques were counted to determine the PFU(plaque forming units)/ml. Results: The results of the present study demonstrated an excellent an antiviral efficacy of NOQ19 at 0.9 mg/ml concentration, eliminating 100% virus. The IC50 of the drug was found to be 0.2 mg/ml. Conclusion: There is limited data around pre-clinical efficacy of polyherbal Ayurvedic drugs. Ayurvedic and herbal formations need to be tested in a preclinical setting to support the human data. The results of the present study demonstrated viral load reduction using NOQ19 in Vero E6 cell lines infected with SARS-CoV-2 virus. These result along with other preclinical and clinical trials could further evaluate the efficacy of NOQ19 as a potential therapeutic option in the fighting the COVID-19 challenge.